Effects of hypoxia on uteroplacental and fetoplacental vascular function during pregnancy - Arenas, Germán A.; Lorca, Ramón A. (Frontiers in Physiology, 2024)
During pregnancy, marked changes in vasculature occur. The placenta is developed, and uteroplacental and fetoplacental circulations are established. These processes may be negatively affected by genetic anomalies, maternal environment (i.e., obesity or diabetes), and environmental conditions such as pollutants and hypoxia. Chronic hypoxia has detrimental effects on the vascular adaptations to pregnancy and fetal growth. The typical pregnancy-dependent rise in uterine blood flow by vascular remodeling and vasodilation of maternal uterine arteries is reduced, leading to increases in vascular tone. These maladaptations may lead to complications such as fetal growth restriction (FGR) and preeclampsia. In this review, the effect of hypoxia on uteroplacental and fetoplacental circulation and its impact on pregnancy outcomes in humans and animal models are discussed. Evidence is provided for several mechanisms that affect pregnancy through hypoxia-induced alterations. Future directions to fill gaps in knowledge and develop therapeutic strategies to prevent or alleviate hypoxia-related pregnancy complications, such as FGR and preeclampsia, are suggested.